Meat consumers and non-meat consumers in Germany: a characterisation based on results of the German National Nutrition Survey II. (7th June 2019) - Koch, Franziska; Heuer, Thorsten; Krems, Carolin; Claupein, Erika
Abstract: Meat consumption in high-income countries is increasingly discussed due to its impact on environment and health as well as ethical considerations. The present paper aims to provide information on meat consumption behaviour, sociodemographic factors related to meat consumption and its associations with health and nutritional behaviour, based on the German National Nutrition Survey II. For 12 915 participants aged 18–80 years, food consumption was assessed by two 24-h recalls and further data by interviews. Participants were distinguished in non-meat consumers and meat consumers; meat consumers were further differentiated as low and high meat consumers (<86 g/d and ≥86 g/d). Group differences were analysed using binary logistic and linear regression models. More non-meat consumers were found among women, young and more educated persons. They showed equal or more preferable health characteristics, had a similar energy intake but ate more plant-based foods compared with meat consumers. More high meat consumers were found among men, young and middle-aged and lower-educated persons. Compared with low meat consumers, they showed equal or less preferable health characteristics, had a higher energy intake and ate more potatoes and sauces/spices and less of most other food groups in relation to their energy intake. To conclude, sociodemographic groups differ in their meat consumption and differences in meat consumption go together with differences in health behaviour and other food consumption.